THE ROLE OF THE PROSECUTION OFFICE IN PSYCHIATRIC HOSPITALIZATION IN THE STATE OF PARANÁ: A BRIEF LEGAL AND PRACTICAL COMMENT (ESMAT Magazine, 2024)
This article aims to address the legal and general aspects of psychiatric hospitalizations for mental health or alcohol and drug addiction. Thus, in an analytical way, Federal Laws nº 11.343/2006 and nº 10.216/2001 and State Law nº 11.189/1995 will be studied, more precisely on the definitions around the modalities of internment and the origin of the supervisory role of the Public Ministry in this folder. In addition, the way in which the Public Ministry of the State of Paraná works in guaranteeing the fundamental rights of hospitalized patients will be demonstrated in order to curb possible abuses in their treatments. In this way, the form of control of hospitalizations by the Public Ministry will be presented and some legislative weaknesses that prevent an even more effective inspection.
Keywords: Psychiatric Admissions. Health. Public Ministry. Oversight